Identifying Influential Factors in the Personal Development Program for National Bank Managers - Afshari, Mahdi; Soleimani, Nader; Shafizadeh, Hamid (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2023)
Objective: The Personal Development Program (PDP) model serves as a coherent and effective tool for human resource development, aligning with the individual and organizational competencies required for managers’ professional development. This study aims to identify the influential factors in the PDP of managers at the National Bank of Iran. Methodology: This applied research employs a qualitative approach. The target population consists of all employees in managerial and specialist positions at the National Bank of Iran, totaling 14,560 individuals. The research sample was selected using both "theoretical sampling" and "snowball sampling" methods, ultimately selecting 30 participants. Data collection was conducted through semi-structured interviews. The validity of the research was confirmed using methods such as peer review and audits by observers. To assess the reliability, the researcher employed strategies from Pitty et al., Charmaz, Lincoln, and Guba, and obtained confirmation. Findings: The results indicate that the professional development program for managers at the National Bank is structured around six key dimensions (knowledge, attitude, communication, professional, leadership, and spiritual competencies) as the central phenomenon. It encompasses three key levels (individual, organizational, and supra-organizational) as causal factors, including six main components: motivation, willingness to learn, interpretability, eagerness to progress, leadership, and critical thinking. Additionally, structural and contextual factors are introduced as the prevailing context and influential factors on the research strategies at three levels. Conclusion: Based on the results, expanding the implementation of the PDP can be considered a qualitative indicator for the professional development of employees in organizations, particularly the National Bank.